2009
DOI: 10.1080/10942910801992942
|View full text |Cite
|
Sign up to set email alerts
|

Total Antioxidant Activity and Total Phenolic Contents in Different Turkish Eggplant (Solanum Melongena L.) Cultivars

Abstract: In this study, total water soluble antioxidant activity and phenolic content of 26 eggplant (Solanum melongena L.) cultivars were investigated. Total water soluble antioxidant activity of the cultivars varied from 2664 to 8247 mmolTrolox/kg, which is a 3.1-fold difference. Cultivars also showed significant variation for total phenolic contents ranging from 615 to 1376 mg/kg, a 2.2-fold difference. The two traits were significantly correlated and results of this study suggested that breeders can use the informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
59
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(76 citation statements)
references
References 27 publications
12
59
2
3
Order By: Relevance
“…The total phenolic content is generally responsible for antioxidants and is well correlated with other antioxidant assays. [19,20] However, in our study, a converse correlation was found when comparing the amount of total phenol with the antioxidant capacity and these two methods (P < 0.05) ( Table 2).…”
Section: Statistical Correlation Between the Tests For Antioxidant Accontrasting
confidence: 71%
“…The total phenolic content is generally responsible for antioxidants and is well correlated with other antioxidant assays. [19,20] However, in our study, a converse correlation was found when comparing the amount of total phenol with the antioxidant capacity and these two methods (P < 0.05) ( Table 2).…”
Section: Statistical Correlation Between the Tests For Antioxidant Accontrasting
confidence: 71%
“…The high amounts of total phenolics in green peppers did not correlate as well with antioxidant capacity and this has previously been reported (Cíz et al, 2010). Significant ranges of vegetable antioxidant capacity have been reported, and the vegetable antioxidant capacities in this study are within published ranges, although the antioxidant capacity of eggplant and green beans were higher than typical (Cíz et al, 2010;Kurilich, Jeffery, Juvik, Wallig, & Klein, 2002;Ninfali, Mea, Giorgini, Rocchi, & Bacchiocca, 2005;Okmen et al, 2009;Ou, Huang, Hampsch-Woodill, Flanagan, & Deemer, 2002;Vinson, Hao, Su, & Zubik, 1998;Wu et al, 2004;Zhou & Yu, 2006).…”
Section: Comparison With Other Vegetablessupporting
confidence: 70%
“…In previous work, other researchers observed significant correlations between antioxidant capacity and its components. Signicant positive correlations were seen between total antioxidant capacity and phenolic content in pepper, [31,32] tomato, [33] eggplant, [34,35] cranberry, [36] and blueberry. [37] In general, these correlations were stronger than the one …”
Section: Correlation Between Parametersmentioning
confidence: 99%